Contribuições da psicologia para o ensino de conteúdos e aprendizagem instrumental : um estudo das publicações dos Cadernos de Pesquisa de 1980 a 2012 - Consonni, Juliana Barbosa (Universidade Federal de São Carlos, 2014)
This paper presents a bibliographic review of scientific publications in the educational field which addresses teaching and learning processes of school subjects related to different theoretical perspectives of Psychology. This work derives from a broader research which investigated the presence of theoretical support of areas such as Sociology and Psychology in publications of three Brazilian scientific journals over the past three decades, they are, Educação & Sociedade, Revista Brasileira de Educação and Cadernos de Pesquisa. From the findings in the broader research which indicate that the presence of psychological science in these publications has decreased in the last decade, our work focuses on the relationship between the instrumental dimension of learning and psychology. Two assumptions pervade this work. The first regards the prospect that social changes in recent decades accelerate the processes of knowledge production and circulation, which also affect academic institutions. In this context, school knowledge gains a central focus in social processes, which is an important tool for people to have social protection and the conditions to strive for better living standards. The second assumption acknowledges that historically school education represents an important area of influence from psychology, addressing topics such as learning educational contents and student behavior, and the same relationship occurred between Brazil s Research in Education and Psychology. Educational Psychology generated many elements that provided the basis for teaching and learning theories, a contribution we believe may also be put into effect in the current context of society. Given these considerations, this research investigates the theoretical elements generated by Psychology for the discussions about the instrumental dimension of education, in the publications of Cadernos de Pesquisa from 1980 to 2012. The methodology included a bibliographical review of the publications on the study object followed by a Content Analysis of the 70 corresponding articles. The most common themes and the psychological theories were analyzed for each decade. The results showed that in the 1980s school failure was often discussed in the publications analyzed, reporting much concern with regards to the learning of school subjects by children of more disadvantaged classes, mainly based on the theory of Piaget and Social Psychology. In the 1990s, Piaget s theory was influential in the discussions about school learning, as was the comparison of this theoretical chain with postulates of the Historical-Cultural theory. The articles analyzed of the year 2000 exhibit discussions about skills and abilities, other knowledge elements that include education, in addition to classroom contents. In the last decade a decrease in the support to psychology-related discussions was also found. We discuss the progression of the presence of Psychology in the last three decades in the Cadernos de Pesquisa, together with possible theoretical implications when considering the assurance of instrumental learning for all students.
Keywords: Pesquisa educacional; Conteúdo escolar; Psicologia; Aprendizagem instrumental; Pesquisa educacional; Psychology; Educational contents; Instrumental learning; Educational research; CIENCIAS HUMANAS::EDUCACAO